Convocation 2001 (Institutional Knowledge at Singapore Management University, 2001)
Faculty at Singapore Management University’s second convocation. SMU welcomed 500 bachelor's degree candidates—the first intake of 100 accountancy students and 400 business students. Convocation 2001 was held at Suntec City Convention Centre on 12 August 2001.